Supplement 2 Section Dental Medicine - Christiana Madjova; Iliyana Atanasova (Journal of IMAB)
Supplement 2 Section Dental Medicine Proceedings of Supplement JofIMAB Publications of papers presented in the Scientific Programme of the 14-th Southeast European Conference Infections and Cancer Ohrid, North Macedonia, 3-6 October 2024